2011
DOI: 10.1007/s12116-011-9088-x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Authoritarianism: The Conceptualization of Hybrid Regimes

Abstract: This paper appraises the state of the field on hybrid regimes by depicting the tensions and blurred boundaries of democracy and authoritarianism "with adjectives." An alternative conceptualization and ordering of regimes are subsequently introduced using a configurative approach. Rather than place regimes on a linear continuum from authoritarianism to democracy, it highlights the multi-dimensional arrangements possible for the construction of regime types. The configurative approach also provides an analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 52 publications
0
51
0
5
Order By: Relevance
“…Similarly, Gilbert and Mohseni (2011) have also found that by redefining of the electoral regime they discovered additional regime dimensions-competitiveness and competition-that are important for classification. They explain that "democracies are competitive regimes with fair competition, whereas authoritarian regimes are uncompetitive regimes with unfair competitions.…”
Section: The Importance Of Multi-dimensionalitymentioning
confidence: 89%
See 4 more Smart Citations
“…Similarly, Gilbert and Mohseni (2011) have also found that by redefining of the electoral regime they discovered additional regime dimensions-competitiveness and competition-that are important for classification. They explain that "democracies are competitive regimes with fair competition, whereas authoritarian regimes are uncompetitive regimes with unfair competitions.…”
Section: The Importance Of Multi-dimensionalitymentioning
confidence: 89%
“…Hybrid regimes are variably understood as diminished subtypes of democracy (Merkel, 2004;Puhle, 2005;Zakaria, 1997); diminished subtypes of authoritarianism (Schedler, 2006); transitional "situations" that are expected to revert back to either democracy or authoritarianism (Armony & Schamis, 2005;Linz, 1973); a residual category of regimes that fit neither democracy nor authoritarianism (Bogaards, 2009;Gilbert & Mohseni, 2011); or as clear-cut instances of authoritarianism (Ezrow & Frantz, 2011;Gandhi, 2008).…”
Section: What Are Hybrid Regimes?mentioning
confidence: 99%
See 3 more Smart Citations